Characterization of Starch Degrading Enzymes from Bacillus amyloliquefaciens UMAS 1002 Isolated From Sago Waste - Mohd Hasnain, Md Hussain; Muhammad Suhaib, Mat Hussin; Awang Ahmad Sallehin, Awang Husaini (2009)
Bacillus amyloliquefaciens UMAS 1002 isolated from sago pith waste was shown to have amylase and cellulase activity. DNA sequence encoding the cellulase gene has previously been isolated with the size of 1527 bp. Screening for amylase gene by polymerase chain reaction using primers based on conserved regions of amylase from B.amyloliquefaciens wild type (J01542.1) has yielded a 2.2kb PCR product. Sequence analysis of this fragment showed potential 14 Open Reading Frames. The longest ORF was 534 bp and the shortest ORF was 168 bp. Alignment of individual ORF using BLASTX showed that one of the ORF with a length of 249 bp has a highest similarity to alpha-amylase from B. amyloliquefaciens FZB2. This fragment is being cloned and expressed in Escherichia coli to determine whether it produces an active amylase.